Surface-initiated growth of copper using isonicotinic acid-functionalized aluminum oxide surfaces - Cathren Gowenlock (Journal of Coatings Technology and Research, 2017)
Isonicotinate self-assembled monolayers (SAM) were prepared on alumina surfaces (A) using isonicotinic acid (iNA). These functionalized layers (iNA-A) were used for the seeded growth of copper films (Cu-iNA-A) by hydrazine hydrate-initiated electroless deposition. The films were characterized by scanning electron microscopy (SEM), electron-dispersive X-ray spectroscopy, atomic force microscopy, X-ray photoelectron spectroscopy, X-ray diffraction, and advancing contact angle measurements. The films are Cu0 but with surface oxidation, and show a faceted morphology, which is more textured (Rq = 460 ± 90 nm) compared to the SAM (Rq = 2.8 ± 0.5 nm). In contrast, growth of copper films by SnCl2/PdCl2 catalyzed electroless deposition, using formaldehyde (CH2O) as the reducing agent, shows a nodular morphology on top of a relatively smooth surface. No copper films are observed in the absence of the isonicotinate SAM. The binding of Cu2+ to the iNA is proposed to facilitate reduction to Cu0 and create the seed for subsequent growth. The films show good adhesion to the functionalized surface.